Persepsi Mahasiswa Program Studi Pendidikan Islam Anak Usia Dini Tentang Urgensi Program Manasik Haji Bagi Siswa Usia Dini - Primanisa, Reiska (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to describe the perceptions of students in the Early Childhood Islamic Education (PIAUD) Program at STAI Sumatera Medan regarding the urgency of the Hajj simulation program (manasik haji) for early childhood learners, viewed from academic, character-building, and financial-benefit aspects within the context of Islamic education. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving ten students and two lecturers from the PIAUD program. The findings reveal that the students have a highly positive perception of the manasik haji program. They view it not merely as a ritual simulation but as a strategic educational medium to introduce the fifth pillar of Islam contextually and to instill Islamic values through real-life experiences. Academically, the program is considered effective in integrating children’s cognitive, affective, and psychomotor aspects through experiential learning. In terms of character formation, it helps cultivate religious awareness, discipline, cooperation, and responsibility from an early age. Regarding financing, students regard the program as a spiritual investment that provides long-term benefits for children, teachers, and educational institutions. The study concludes that PIAUD students at STAI Sumatera Medan possess strong academic and spiritual awareness of the importance of the manasik haji program as a meaningful experiential learning medium for shaping a Qur’anic generation with Islamic character.